Decision Support System to Determine the Achievement of Students Using Simple Multi-Attribute Rating Technique (SMART) - Jahir, Abdul; Setiawan, Ito; Arta, Anisa Dayu (International Journal of Informatics and Information Systems, 2019)
The problem is in determining the achievement of students by organizing the consultation between teachers. The purpose of this research is to assist the decision-making process of determining the achievement of students with SMART method implementation. The methods of collecting data are interviews, documentation, and observations. The method of system development used is the waterfall method by using the system design tools in the form of DFD and ERD. The software used in the creation of this application is Visual Studio and SQL server express. The results of this study are SMART ranking methods. The decision support process is more objective because it complies with predefined criteria.Decision Support System to Determine the Achievement of Students Using Simple Multi-Attribute Rating Technique (SMART)